O impeachment de Fernando Collor: aspectos econômicos, políticos e jurídicos que levaram à queda do presidente - Pujol, Marcus Vinicius Comenale (2017)
After more than two decades of dictatorship, Fernando Collor is consecrated as the youngest and the first president democratically elected by the people since Jânio Quadros. After the violent election campaign of 1989, Collor begins to face the crises that would lead to his fall after a short mandate. The combination of a very serious economic crisis, lack of political support and judicial battles for corruption scandals, led the country to ungovernability, giving rise to the use of the instrument of impeachment